Rereading Gender in Qur’anic Exegesis: Philosophical and Critical Hermeneutic Perspectives - Mohammad Alfin Niam; Abd. Muid Nawawi; Makmunzir (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2025)
This study examines the application of a gender approach in Qur’anic exegesis aimed at maintaining a balance between social critique and the ta`abbudī dimension. The background of this research is rooted in feminist critiques of classical tafsir, which often reproduce patriarchal biases through androcentric interpretations and the politicization of the text by male elites. This qualitative study employs Hans-Georg Gadamer’s philosophical hermeneutics and Jürgen Habermas’s critical theory as analytical frameworks. A literature review was conducted on classical and contemporary tafsir works, as well as related scholarly literature, to classify verses related to women into the social (mu`āmalah) and ta`abbudī realms and to evaluate the proportional application of the gender approach in these interpretations. Findings reveal that Gadamer’s hermeneutics affirms the dialogical process between tradition and modern horizons in gender interpretation while delineating proper boundaries respecting the authority of ta`abbudī texts. Habermas’s framework highlights the role of gender critique as an emancipatory instrument in the social realm but emphasizes that communicative rationality does not apply to the normative and transcendent ta`abbudī domain. Consequently, this study underscores the importance of maintaining methodological and epistemological balance to ensure that gendered tafsir neither diminishes nor disregards the authority of revelation, while fostering constructive dialogue between religious tradition and modern demands.